Implementation Of Schoolhealth Business Program Management In SMP Negeri 34, City Of Palembang - Sugiarti; Fitria, Happy; Wahidy, Achmad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
UKS is a unit that provides students with health services to improve their health. Research findings at SMP Negeri 34 Palembang showed that: UKS management began from: (a) preparation (b) execution, (c) control was not optimal. Obstacles to the introduction of the UKS program are due, among other things, to insufficient clean and safe living practices, issues with human resources, inadequate facilities and infrastructure, insufficient documentation. Coordination was not maximal between related agencies, the UKS program was insufficient, The UKS VISION is not clear, the preparation is not yet strategic in order to achieve the VISION, limited funds in the process of implementing the UKS Program, there is still inadequate, insufficient time for Puskesmas employees to concentrate on supporting UKS, as well as clean and safe conduct